Sosio-Ekologi Masyarakat Sekitar Sabuk Hijau (Greenbelt) Waduk Jatigede - Budiyanti, Anita (Wanamukti: Jurnal Penelitian Kehutanan, 2018)
Green Belt area of the Jatigede Reservoir are located at an elevation of 260-262.5 masl covering 5 administrative districts namely Jatigede, Jatinunggal, Wado, Darmaraja and Cisitu. Spatialy is included into a local protected area which one the ownership of land is under the authority of the reservoir management. The phenomenon that occurred earlier in the dams in Indonesia are the green belt fields has degradation such as occupational settlement and conversion of agricultural land by civil society which does not convey the principles of soil and water conservation. Green belt area as buffer zone and an interface between the core zone (aquatic) and the outside of reservoir area (community settlement). The socioecological interaction between human and natural resources will always occur in the buffer zone. The object of this research is to learn of socio-ecology at green belt land as multifunctional area both for conservation and production function and in its utilization involving people affected by the construction of Jatigede dam. The method used is a concurrent quantitative-qualitative combination to explore the biophysical, social, economic and cultural characteristics and perception of the stakeholders about exictence the green belt of the Jatigede dam. The socio-ecology of civil society not use concept in land use plan green belt of jatigede reservoir is to make zonation based on biophysical factor that is zones of conservation and production. Â Keywords : Green belt, Jatigede Reservoir, Socio-ecology landscape